1999
DOI: 10.1080/00071669987061
|View full text |Cite
|
Sign up to set email alerts
|

Optimum inclusion of field peas, faba beans, chick peas and sweet lupins in poultry diets. I. Chemical composition and layer experiments

Abstract: 1. Experiments were undertaken to determine the chemical composition and apparent metabolisable energy (AME) of field peas, faba beans, sweet lupins and chick peas and the production of hens when each was included in nutritionally similar diets at 250 g/kg in 2 experiments. 2. Amino acid composition, crude protein and AME agreed well with previously published measurements. Detailed analysis of the non-starch polysaccharides (NSPs) showed that sweet lupins were much higher than the other grain legumes in the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 10 publications
7
41
1
3
Order By: Relevance
“…In the study of Fru-Nji et al (2007) mortality rates were not reported, indicating that FB inclusion had no major problems on the mortality of the hens in their study (half were LSL and the other half Lohmann Brown). In contrast to our study, FB inclusion had no adverse effect on mortality in the studies of Campbell et al (1980), Perez-Maldonado et al (1999), and Laudadio and Tufarelli (2010). Campbell et al (1980) used SCWL laying hens, Hy-line, and FB at 250 g kg -1 in the diet.…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…In the study of Fru-Nji et al (2007) mortality rates were not reported, indicating that FB inclusion had no major problems on the mortality of the hens in their study (half were LSL and the other half Lohmann Brown). In contrast to our study, FB inclusion had no adverse effect on mortality in the studies of Campbell et al (1980), Perez-Maldonado et al (1999), and Laudadio and Tufarelli (2010). Campbell et al (1980) used SCWL laying hens, Hy-line, and FB at 250 g kg -1 in the diet.…”
Section: Resultsmentioning
confidence: 39%
“…Campbell et al (1980) used SCWL laying hens, Hy-line, and FB at 250 g kg -1 in the diet. Perez-Maldonado et al (1999) used SIRO-CB pullets, and FB cv. 'Fiord' at 250 g kg -1 in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of lupin diets on egg production performance in laying hens that we observed are inconsistent with some previous studies. In a previous report, 25% lupin supplementation in layer diets resulted in higher performance in a 40- week experiment: hen per day egg production was higher than 90% and feed intake was approximately 120 g/hen per day (Perez-Maldonado et al 1999). In another study, feed supplemented with up to 30% white lupin in diets resulted in good egg production (Prinsloo et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Field pea has been shown to be an effective replacement for soybean meal (SBM; Corbett et al, 1995;Khorasani et al, 1992) and SBM and canola meal combinations (Petit et al, 1997) in diets fed to lactating dairy cows. Optimum inclusion level of field pea in non-ruminant diets have been suggested to be 250-333 g/kg (Castanon and Perez-Lanzac, 1990;Perez-Maldonado et al, 1999;Farrell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%